Prevalence and Molecular Identification of Giardiasis Isolates from Stray Dogs in Erbil Province, Kurdistan Region, Iraq - Zuber I. Hassan (Polytechnic Journal)
Giardia lamblia is the intestinal, flagellated protozoan parasite. It should make a species complex and comprises eight assemblages (A-H). In the current study, out of 153 examined samples, 16 (10.46%) and 36 (23.53%) specimens were positive by concentration and polymerase chain reaction (PCR) technique for giardiasis, respectively. The highest rate of infection was found in a rural area (14.38%) than in urban areas (9.15%). As well as, the infection rate in males (25/153) was higher compared to that of female dogs (11/153). Regarding fecal consistency, the highest rate (18.3%) of giardiasis was observed in diarrheic dogs, while the lowest rate of giardiasis (5.23%) was observed among non-diarrheic dogs. The PCR products were sequenced for 20 samples and further examined by sequence analysis, 16 isolates under the accession number (MN629930), independent of the host, exhibited G. lamblia GenBank ID: M36728, while in four samples under the accession number (MN629931), nucleotide substitutions generate polymorphism at position 542 and 561 (C → T) and (A → G) at position 684. The similarity between MN629931 and AY072723 genotype A2 was 99.9% which was one nucleotide substitution at position 542 (C → T). The sequencing of the PCR products recognized two assemblages in dogs suggested the possible role of dogs as the reservoir for human giardiasis in Erbil Province which is the first records in the Kurdistan Region, Iraq.